Gain Enhancement of Patch Antenna using Novel Glass Fiber Reinforced Polymer (GFRP) based Metasurface - A. K. M. S. Ali; I. Ahmed; S. Ali; M. Khalid (Advanced Electromagnetics)
In this paper, the authors have presented extensive work done involving the design, simulation, development, and performance measurement of a novel Glass Fiber Reinforced Polymer (GFRP) composite-based metasurface patch antenna.  The authors have first designed GFRP composite-based metasurface patch antenna and simulated the design to measure its performance. Then the same antenna has been indigenously developed following the design specifications. Using the developed antenna, measurements have been recorded and performance has been analysed. Moreover, considering the significance of benchmarking, the authors have also compared the performance of the design and developed GFRP composite-based metasurface patch antenna results against the performance of Linear C-band patch antenna and a GFRP-based metasurface patch antenna. The results obtained through simulation and testing show characteristic similarity thus validating the approach adopted for the printing of copper on GFRP composite. The results also show that using GFRP composite as a metasurface on top of simple microstrip patch antenna results in an overall 39% gain enhancement compared to simple microstrip patch antenna gain.